Potential Utilization of APOBEC3-Mediated Mutagenesis for an HIV-1 Functional Cure - Ikeda, Terumasa; Yue, Yuan; Shimizu, Ryo; Nasser, Hesham (Frontiers in Microbiology, 2021)
The introduction of combination antiretroviral therapy (cART) has managed to control the replication of human immunodeficiency virus type 1 (HIV-1) in infected patients. However, a complete HIV-1 cure, including a functional cure for or eradication of HIV-1, has yet to be achieved because of the persistence of latent HIV-1 reservoirs in adherent patients. The primary source of these viral reservoirs is integrated proviral DNA in CD4+ T cells and other non-T cells. Although a small fraction of this proviral DNA is replication-competent and contributes to viral rebound after the cessation of cART, >90% of latent viral reservoirs are replication-defective and some contain high rates of G-to-A mutations in proviral DNA. At least in part, these high rates of G-to-A mutations arise from the APOBEC3 (A3) family proteins of cytosine deaminases. A general model has shown that the HIV-1 virus infectivity factor (Vif) degrades A3 family proteins by proteasome-mediated pathways and inactivates their antiviral activities. However, Vif does not fully counteract the HIV-1 restriction activity of A3 family proteins in vivo, as indicated by observations of A3-mediated G-to-A hypermutation in the proviral DNA of HIV-1-infected patients. The frequency of A3-mediated hypermutation potentially contributes to slower HIV-1/AIDS disease progression and virus evolution including the emergence of cytotoxic T lymphocyte escape mutants. Therefore, combined with other strategies, the manipulation of A3-mediated mutagenesis may contribute to an HIV-1 functional cure aimed at cART-free remission. In this mini-review, we discuss the possibility of an HIV-1 functional cure arising from manipulation of A3 mutagenic activity.